An X‐ray harmonic separator for next‐generation synchrotron X‐ray sources and X‐ray free‐electron lasers. (28th February 2018) - Inoue, Ichiro; Osaka, Taito; Tamasaku, Kenji; Ohashi, Haruhiko; Yamazaki, Hiroshi; Goto, Shunji; Yabashi, Makina
Abstract : A new optical technique used to extract a specific harmonic of undulator radiation is proposed and the concept was experimentally confirmed using X‐ray pulses from SACLA. Abstract : An X‐ray prism for the extraction of a specific harmonic of undulator radiation is proposed. By using the prism in a grazing incidence geometry, the beam axes of fundamental and harmonics of undulator radiation are separated with large angles over 10 µrad, which enables the selection of a specific harmonic with the help of apertures, while keeping a high photon flux. The concept of the harmonic separation was experimentally confirmed using X‐ray beams from the X‐ray free‐electron laser SACLA.